Shifting Perceptions of Effective EFL Teacher Characteristics: A Case Study of Gen Z Pre-Service Teachers at UNM - Mansyur, Mansyur; Sunra, La; Amalia, Suci; Yuli Wahyuni, Ika (Pascasarjana Universitas Negeri Makassar, 2025)
This study explored the shifting perceptions of Gen Z pre-service teachers regarding the characteristics of effective EFL teachers and their expectations of ideal teaching styles at Universitas Negeri Makassar (UNM). The research employed a qualitative approach, utilizing semi-structured interviews with five pre-service teachers. The findings revealed that Gen Z values student-centered learning, the integration of technology, and the empathy demonstrated by teachers. They expressed a preference for teaching methods that foster active student participation and collaborative learning, in contrast to more traditional teacher-centered models. Additionally, the study highlighted the importance of adaptability in teachers, as well as their ability to address diverse student needs. These results suggest that teacher education programs must adapt to Gen Z's expectations by integrating technology, focusing on empathy, and fostering student-centered approaches in teacher training curricula.